2023
DOI: 10.3390/ani13091471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing the Methionine Level and Reducing the Threonine Level in the Diet of Fast-Growing Rabbits

Abstract: The main aim of this work was to evaluate a novel combination of the first limiting amino acids (lysine, methionine, and threonine) in fast-growing rabbits (combination MHL, shown to minimise levels of plasmatic urea nitrogen in previous research, medium level of lysine, high level of methionine, and low level of threonine) and compare it with current recommendations (combination MMM, medium level of all amino acids). A total of 165 weaned rabbits (28 d old) from a paternal line selected for growth rate were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As a result, the obtained sanitary risk index (37%) was comparable to other reported values in the literature for this same line (on av. 35%) [9,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the obtained sanitary risk index (37%) was comparable to other reported values in the literature for this same line (on av. 35%) [9,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Oversized levels: Another hypothesis suggests that the levels of this amino acid are oversized, causing an excess that must be catabolised. This hypothesis seems to be less plausible, as there are recent works in growing rabbits of this same age and selected for similar traits that showed that the lysine levels used in this experiment match their requirements 57 , 58 . (iii) Higher digestibility of synthetic lysine: The increased degradation might be a consequence of the higher digestibility of the synthetic lysine added to Diet B by adding l -lysine HCl (4.7 g per kg).…”
Section: Methodsmentioning
confidence: 97%
“…(ii) Oversized Levels: Another hypothesis suggests that the levels of this amino acid are oversized, resulting in an excess that must be catabolised. However, this hypothesis seems less plausible, as the nutritional requirements for methionine are well established and closer to the higher levels 58 . (iii) Higher Digestibility of Synthetic Methionine: The increased degradation might be a consequence of the higher digestibility of the synthetic methionine added at each level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation